An Improvement Approach for Wide-Angle Impedance Matching Using ELC Metasurface Slabs for SIW Slot Array Antennas - Yi Liu; Hu Yang; Zusheng Jin; Jiang Zhu (International Journal of Antennas and Propagation)
The effects of mutual coupling in beam scanning arrays increase degradation in gain as the beam is scanned off the broadside. A simple and effective approach for a deployed SIW slot array antenna through the use of artificially structured materials is proposed to improve its performance of wide-angle scanning in the E-plane. Metasurface slabs of one-tenth wavelength electric-inductive-capacitive (ELC) resonators are vertically placed halfway between the adjacent waveguides without changing the antenna structure to realize wide-angle impedance matching (WAIM). The ELC metasurface is designed to operate at a linear region rather than at a resonance region to use its transmission property for greatly weakening mutual couplings. Inserting metasurface slabs between two adjacent waveguides to reduce the mutual coupling can achieve impedance matching at large scan angles. A 10 × 10 SIW slot array operating at X-band is modelled and simulated to study how the vertically placed ELC metasurface slabs over the antenna affect the array’s beam scanning performance. The simulated results show that the scan range of the antenna is extended from −50° to 50° to −70° to 70° under the criteria that radiating efficiency is greater than 80%.